2017
DOI: 10.5430/jnep.v7n10p119
|View full text |Cite
|
Sign up to set email alerts
|

Developing genetic counseling for male BRCA1/2 mutation carriers based on their own experiences

Abstract: Background: Previous studies of genetic counseling (GC) for male BRCA1/2 mutation carriers have focused on their level of satisfaction with the GC and its content. The aim of this study was to examine the GC experiences of male BRCA1/2 mutation carriers, and their suggestions for improving GC, more broadly. Methods: Data were collected by themed interviews of Finnish male BRCA1/2 mutation carriers (n = 31), and subjected to inductive content analysis. Results: The results indicated that the participants had a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…There were also expressions that identification as a carrier induced no adverse reactions, as it merely seemed to be like a feature of the participants. Our previous findings (Kajula et al 2017) highlighted needs for post-test genetic counseling and individual psychosocial support for the male carriers in various life situations. The present study and several others (Liede et al 2000;Shiloh et al 2013) have shown that responses to genetic test results are highly individual, and there may be wide ranges in variables such as the processing timing and duration.…”
Section: Category: Social Well-beingmentioning
confidence: 72%
See 2 more Smart Citations
“…There were also expressions that identification as a carrier induced no adverse reactions, as it merely seemed to be like a feature of the participants. Our previous findings (Kajula et al 2017) highlighted needs for post-test genetic counseling and individual psychosocial support for the male carriers in various life situations. The present study and several others (Liede et al 2000;Shiloh et al 2013) have shown that responses to genetic test results are highly individual, and there may be wide ranges in variables such as the processing timing and duration.…”
Section: Category: Social Well-beingmentioning
confidence: 72%
“…Finally, findings from our study and previous studies (Kajula et al 2016(Kajula et al , 2017 could be used to develop a tentative model of genetic counseling for male BRCA1/2 mutation carriers, tested with members of this population.…”
Section: Clinical Implications and Research Recommendationsmentioning
confidence: 81%
See 1 more Smart Citation
“…Information provided in the adult intensive care unit (ICU) setting falls under patient and family member counselling, which is a broad term for the education, guidance, tips, and information that patients and their family members receive from intensive care professionals (ICPs). 1,2 In this study, counselling concerns the mutual interactions between patients and family members and ICPs, whereas information only concerns relevant materials and explanations received by patients from ICPs. The counselling provided to adult ICU patients and their family members by ICPs can be described based on the content, implementation, benefits and resources.…”
Section: Introductionmentioning
confidence: 99%
“…The counselling provided to adult ICU patients and their family members by ICPs can be described based on the content, implementation, benefits and resources. [1][2][3][4] ICU patients and their family members need good quality counselling to both adapt to the distressing situation during intensive care and recover from it. Provided counselling is based on the patients' and family members' needs and, as such, the ICPs' background and competence are key factors in determining the quality of provided counselling.…”
Section: Introductionmentioning
confidence: 99%